Likha a cultural and arts center for the Angono Lakeshore District - Joveres, Kristina Fatima N.
Likha, a Filipino term which means "to create" seems to be a very fitting word for a small town full of magnificent creations. Angono, despite being a relatively small municipality, is abundant in artistic and cultural heritage that the townspeople take pride in. It is considered as the Art Capital of the Philippines, the ASEAN Culture Capital, the site of the oldest known work of art., the hometown of two well-known National Artists, an artist's haven. It holds a huge potential but, at the same time, faces issues that need to be addressed as well. this includes weak tourism industry despite the number of tourist destinations in town, the continuous deterioration of Laguna Lake, the lack of identity as an Art Capital in the lakeshore district, the lack of central facility that would institutionalize the artistic culture of Angono, and the lack of venue for young emerging visual artists to showcase their art forms, among other things. The proposed Cultural and Arts Center for the Lakeshore District hopes to address these issues and be a catalyst in the revitalization of the lakeshore district. The facility also hopes to embody the art and culture of Angono and evoke a unique experience for the users.